Changes in inflammatory response and performance to field tests induced by a concomitant training block in élite handball players in Benin - TONON, Brigitte Affidéhomé; Linta, Léonce Sèdjro Odjouola; HOUNTOHOTEGBE, Tatiana; GOUTHON, N. M. POLYCARPE; BIGOT, KOFFI ANDRÉ; NOUATIN, BASILE; BIO NIGAN, ISSIAKO (My University, 2021)
The effects of different training methods on immune function in African elite handball players have been little evaluated. The aim of this study was to determine the effects of a six-week concomitant training (CT) block on parameters associated with the inflammatory response and performance on field tests in elite handball players in Benin. This was a controlled interventional study, undertaken with 18 international handball players (21.4 ± 3.0 years), randomized into two groups: interventional (IG) and control (CG). Players of the intervention group (IG) participated in a concomitant training block (CT) and those who served as controls (CG), followed the usual content of their training sessions (UC). Interleukins Il-6 and Il-10, tumor necrosis factor (TNF-α), as well as performance in five field tests, were determined at the beginning and end of the six-week of training. Changes in inflammatory response parameters recorded in IG were similar to those in CG (P > 0.05). Improvements recorded were greater in the IG group than in CG, for 2VO max  (+4.3% versus +1.5%; P = 0.01), medicine-ball throwing distance (+15.9% versus +4.3%; P = 0.004) and height in counter movement jump (+7.0% versus +0.5%; P = 0.004). Handball coaches can therefore use concomitant training as an effective method of developing 2VO max  and explosive strength capacity without fearing an impairment of immune function in the handball players studied.
Keywords: Inflammatory Response; Fitness Capacity; Training Method; Handball; Sub-Saharan Africa